Protective Yeasts Control V. anguillarum Pathogenicity and Modulate the Innate Immune Response of Challenged Zebrafish (Danio rerio) Larvae - Caruffo, Mario; Navarrete, Natalie C.; Salgado, Oscar A.; Faúndez, Nelly B.; Gajardo, Miguel C.; Feijóo, Carmen G.; Reyes-Jara, Angélica; García, Katherine; Navarrete, Paola (Frontiers in Cellular and Infection Microbiology, 2016)
We investigated mechanisms involved in the protection of zebrafish (Danio rerio) larvae by two probiotic candidate yeasts, Debaryomyces hansenii 97 (Dh97) and Yarrowia lypolitica 242 (Yl242), against a Vibrio anguillarum challenge. We determined the effect of different yeast concentrations (104 – 107 UFC/mL) to: i) protect larvae from the challenge, ii) reduce the in vivo pathogen concentration and iii) modulate the innate immune response of the host. To evaluate the role of zebrafish microbiota in protection, the experiments were performed in conventionally raised and germ-free larvae. In vitro co-aggregation assays were performed to determine a direct yeast-pathogen interaction. Results showed that both yeasts significantly increased the survival rate of conventionally raised larvae challenged with V. anguillarum. The concentration of yeasts in larvae tended to increase with yeast inoculum, which was more pronounced for Dh97. Better protection was observed with Dh97 at a concentration of 106 CFU/mL compared to 104 CFU/mL. In germ-free conditions V. anguillarum reached higher concentrations in larvae and provoked significantly more mortality than in conventional conditions, revealing the protective role of the host microbiota. Interestingly, yeasts were equally (Dh97) or more effective (Yl242) in protecting germ-free than conventionally-raised larvae, showing that protection can be exerted only by yeasts and is not necessarily related to modulation of the host microbiota. Although none of the yeasts co-aggregated with V. anguillarum, they were able to reduce its proliferation in conventionally raised larvae, reduce initial pathogen concentration in germ-free larvae and prevent the upregulation of key components of the inflammatory/anti-inflammatory response (il1b, tnfa, c3, mpx and il10, respectively). These results show that protection by yeasts of zebrafish larvae challenged with V. anguillarum relates to an in vivo anti-pathogen effect, the modulation of the innate immune system, and suggests that yeasts avoid the host-pathogen interaction through mechanisms independent of co-aggregation. This study shows, for the first time, the protective role of zebrafish microbiota against V. anguillarum infection, and reveals mechanisms involved in protection by two non-Saccharomyces yeasts against this pathogen.